The Effect of Transformational Leadership Style and Organizational Communication on the Performance of Employees at the Majalengka Regency Disaster Management Agency - Ari Permana; Agi Syarif Hidayat (Publikasi Indonesia, 2026)
This study aims to analyze the influence of transformational leadership and organizational communication on employee performance at the Regional Disaster Management Agency (BPBD) of Majalengka Regency. This research is motivated by the demand to improve the performance of BPBD personnel in the face of dynamic and complex working conditions, necessitating an effective organizational leadership and communication style to support the achievement of optimal employee performance. This study uses a quantitative approach with an associative method. The population in this study consists of all employees of BPBD Majalengka Regency, totaling 70 people, all of whom were used as the research sample through a saturated sampling technique. The research data were obtained through the distribution of questionnaires using a Likert scale and analyzed using multiple linear regression analysis with the assistance of the SPSS program. The results of the study show that transformational leadership partially does not have a significant effect on the performance of BPBD Majalengka Regency employees. Meanwhile, organizational communication has a positive and significant effect on the performance of BPBD employees in Majalengka Regency. The coefficient of determination indicates that transformational leadership and organizational communication together are able to explain 22% of the variance in employee performance, while the remainder is influenced by other variables outside the research model. Based on the results of this study, it can be concluded that organizational communication plays an important role in improving the performance of BPBD Majalengka Regency employees.